Estimation of some plant nutrition and heavy metals in Euphrates River at AL-Ramadi and Khalidiah Cities - Majeed Mahmoud Khalaf; Riedh A. Abdul - Jabbad (Tikrit Journal of Pure Science, 2023)
This study was carried out in Euphrates River at Al-Jazira region in between the cities of Al-Ramadi and khalidiah in AL-Anbar province.  Seven stations were selected. The first one was west to AL-Ramadi, and the Last one was at Al-Khalidiah bridge. The study was carried out during the period from September 2013 to June 20l4.  Results of the plant nutrition of nitrite, phosphate and silica were (0.01-0.3) μg nitrogen atom-nitrite, (0.11-0.79) μg phosphorus -atom- phosphate, and (0.58-1.39) mg/L. Heavy metals of chrome and cobalt were in between the allowed values of the Iraqi drinking water characterization and were (0.00-0.05) mg/L and (0.00-0.02) mg/L receptively. The values of the other metals as Lead, Nickel, and Cadmium were extended beyond the allowed characterization of standard Iraqi drinking water and were (0.007-0.950), (0.00-0.036), and (0.004-0.04) mg/L respectively. Statistical analyses (at the significance level of 0.01 and 0.05) proved to have no significant differences between the stations for all factors, while significant differences were found with time (P≤ 0.05)  for alt factors.